2016
DOI: 10.1111/codi.13470
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing acute appendicitis: surgery or imaging?

Abstract: This article discusses the role of imaging in the diagnostic work-up of patients who are suspected of acute appendicitis, comparing national snapshot studies as a model to do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
1
33
0
2
Order By: Relevance
“…The finding in this cohort that incidence peaks among persons aged 10-19 years, and is greater among men compared to women, is consistent with previous epidemiological literature [1,32,36,37]. In 2010, a new Dutch guideline on treatment of appendicitis was published, which incorporates ultrasound or CT imaging in the standard diagnostic process [38,39]. It is plausible that fewer patients were operated as a result due to better diagnosis and a fall in the proportion of appendectomy for appendix sana.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding in this cohort that incidence peaks among persons aged 10-19 years, and is greater among men compared to women, is consistent with previous epidemiological literature [1,32,36,37]. In 2010, a new Dutch guideline on treatment of appendicitis was published, which incorporates ultrasound or CT imaging in the standard diagnostic process [38,39]. It is plausible that fewer patients were operated as a result due to better diagnosis and a fall in the proportion of appendectomy for appendix sana.…”
Section: Discussionsupporting
confidence: 86%
“…It is plausible that fewer patients were operated as a result due to better diagnosis and a fall in the proportion of appendectomy for appendix sana. A large Dutch cohort study (n = 1943) performed in 2014 demonstrated a low negative appendectomy rate of 3% [38,39]. Another factor that might play a role is the growing popularity of non-operative treatment and fading dogma 'when in doubt, take it out'.…”
Section: Discussionmentioning
confidence: 99%
“…The overall NAR in UK adults aged 16–45 years was 20·0 per cent, significantly higher than the rate recorded in other countries that participated in the RIFT Study. This represents one of the world's highest NARs. Although simple and complex appendicitis may represent distinct pathologies, some surgeons believe that delaying surgery may increase the risk of appendiceal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, concerns over the radiation exposure associated with CT have limited its routine use. Although modern low‐dose protocols have reduced radiation exposure whilst maintaining diagnostic performance, CT rates are lower in the UK than in many other high‐income countries, and this is associated with higher normal appendicectomy rates (NARs).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of cases showed clinical features of acute and clinical chronic appendicitis, especially in ileocecal valve cancer. Acute appendicitis is the most commonly encountered condition in general surgery and it may affect anyone, regardless of their age [4] . Unfortunately, the misdiagnosis of right colon cancer as appendicitis or appendiceal abscess does occur occasionally in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%